Budaya Patriarki Dalam Pembungkaman Perempuan Pada Film “ The Stoning Of Soraya M” (Kajian Komunikasi Gender) - Nurul Fatonah; Susi Andrini (Journal of Feminism and Gender Studies, 2022)
This study aims to examine the meaning of patriarchal culture in silencing women in the film "The Stoning Of Soraya M." The method used is qualitative with the semiotic approach of Charles S Pierce and the communication theory of Gender (Standpoint Theory), Sandra Harding and Julia Wood which interpret the symbols or signs of treatment and the texts in the film for analysis. The results of this research indicate that the patriarchal culture in the film "The Stroming Of Soraya M," women are in the lowest position compared to men.